Sustainable Human Resource Management and Its Relationship to Achieving Organizational Sustainability: The Interactive Role of Electronic Management Information Systems – An Applied Study on a Sample of Employees at the General Company for Electricity Tra - Abdul kareem, Assistant Lecturer: Mohammed (The Gulf Economist, 2025)
The study aims at examining the relationship between Sustainable Human Resource Management and Organizational Sustainability through the interactive role of Electronic Management Information Systems among the employees of the Basra Electricity Distribution Company. Accordingly, the research adopts a descriptive-analytical method to collect and analyze data, relying on a questionnaire-based approach. A total of 250 questionnaires were distributed to the study sample, of which 200 were received and deemed suitable for analysis. To develop a conceptual model, a set of main and sub-hypotheses were formulated based on a review of previous studies related to the research topic. Various statistical tools were applied using SPSS (Version 23) to analyze the data and test the validity of the study hypotheses. The results of the statistical analysis indicate that the studied company prioritizes sustainability in its human resources to achieve Organizational Sustainability and actively seeks to enhance this process by leveraging Electronic Management Information Systems.